(untitled) (Annual of the Faculty of Philosophy in Skopje, 2008)
The beginnings of the archive education, which chronologically can locate in the second half ofXVIH and XIX century, have a row of difficulties and angriness. In the text it is represented a sort cut of the development of the archive education in menu European construes (Italy, France, Holland and others), by witch is represented that many times and in the frames of one archive service there exists many models of education of the archivists, which have differences in the content, in the shape, the ways on which the programs have been performing, as like as the aims which are set up in the frames of the educational process. With the studies ’ development the archive is shaping theoretically, but and the archivists begging to search for its professional identity. In the second half of the XX century they came to such changes, when we have fast progress of the informational sciences, which affected to the archive structure, and also to the education. From this begins the redefinition of the profession, and also of the structure and the context of the archive education. The archive education suffers one total changes in the last two - three decades.